RAD51 Testing in Patients with Early HER2-Negative Breast Cancer and Homologous Recombination Deficiency: A Post Hoc Analysis of the GeparOLA Trial - Villacampa, Guillermo; Llop-Guevara, Alba; Filmann, Natalie; Herencia-Ropero, Andrea; Fasching, Peter; Karn, Thomas; Marmé, Frederik; Klare, Peter; Müller, Volkmar; Stefek, Andrea; Schem, Christian; Uleer, Christoph; et al. (Clinical Cancer Research, 2025)
PURPOSE: The randomized GeparOLA trial reported comparable pathologic complete response (pCR) rates with neoadjuvant treatment containing olaparib versus carboplatin. In this study, we evaluate the association between functional homologous recombination deficiency (HRD) by RAD51 foci and pCR and the potential of improving patient selection by combining RAD51 and stromal tumor-infiltrating lymphocytes. PATIENTS AND METHODS: This is a post hoc blinded biomarker analysis from the randomized GeparOLA trial. Patients with early-stage HER2-negative breast cancer and HRD assessed by Myriad MyChoice or BRCA1/BRCA2 mutations were randomized 1:1 to receive (i) paclitaxel plus olaparib or (ii) paclitaxel plus carboplatin, both followed by epirubicin/cyclophosphamide. Functional HRD was predefined as a RAD51 score ≤10% (RAD51-low). RESULTS: Overall, 90 of 97 (92.8%) samples were evaluable for RAD51 testing, and 72 of 90 (80.0%) were RAD51-low. The pCR rate in patients with RAD51-low tumors was 66.7% (48/72), whereas it decreased to 22.2% (4/18) in those with RAD51-high. In the multivariable model including clinicopathologic factors and treatment, the RAD51 score remained significantly associated with pCR (OR = 12.03; 95% confidence interval, 2.60-55.73; P = 0.002). Patients with RAD51-low and high stromal tumor-infiltrating lymphocytes in their tumors achieved a pCR rate of 75.0% (27/36). Similar results were observed for olaparib or carboplatin. In the exploratory disease-free survival analysis, no differences were observed between RAD51 groups (high vs. low: HR = 0.85; 95% confidence interval, 0.25-2.97). CONCLUSIONS: In a preselected population with HRD, according to a genetic test, RAD51 testing identifies patients with different pCR rates under PARP inhibitor-based or platinum-based therapies. Future biomarker-driven studies should consider this information to refine stratification factors and to improve patient selection.
CRIS-Team Scopus Importer:2025-03-28